The Role of Virtual Reality in Screening, Diagnosing, and Rehabilitating Spatial Memory Deficits - Jonson, Miles; Avramescu, Sinziana; Chen, Derek; Alam, Fahad (Frontiers in Human Neuroscience, 2021)
Impairment of spatial memory, including an inability to recall previous locations and navigate the world, is often one of the first signs of functional disability on the road to cognitive impairment. While there are many screening and diagnostic tools which attempt to measure spatial memory ability, they are often not representative of real-life situations and can therefore lack applicability. One potential solution to this problem involves the use of virtual reality (VR), which immerses individuals in a virtually-simulated environment, allowing for scenarios more representative of real life without any of the associated risks. Here, we review the evidence surrounding the use of VR for the screening and diagnosis of spatial memory impairments, including potential limitations and how it compares to standard neuropsychological tests. We will also discuss the evidence surrounding the potential use of VR in rehabilitation of spatial memory deficits, which has not been well studied, but which could be game-changing if proven successful.